Effectiveness of Accompanying Pregnant Women with High Parity on ANC Visit Coverage - Porouw, Hasnawatty Surya; Astuti, Eka Rati; Tompunuh, Magdalena Martha; Titisari, Ira; Rahmawati, Rahajeng Siti Nur (State Islamic University of Sunan Ampel, 2024)
Efforts to accelerate the reduction of MMR are carried out by ensuring that every mother is able to access quality maternal health services, such as health services for pregnant women, birth assistance by trained health workers in health service facilities, post-natal care for mothers and babies, special care and referrals if complications occur, and family planning services including postnatal family planning. The aim of the research is to analyze the effectiveness of assisting pregnant women with high parity on the coverage of Antenatal care visits as an effort to early detect pregnancy complications in the work area of the Boalemo Regency Health Center. The design used in this research is a quasi-experimental design with a non-equivalent control group design. The sample is 32 respondents who received treatment, and 32 respondents who did not receive treatment. The sampling technique in this research was taken using Stratified Random Sampling which met the inclusion criteria. Data collection techniques use SOP, questionnaires and in-depth interviews. The results show that the t-test value is sig. 2 (tailed) is 0.008, meaning that the alpha of 5% is met so that there is a significant difference in the coverage of antenatal care visits between mothers who are given cadre assistance and those who are not given cadre assistance. The conclusion is that there is an influence of assistance by health cadres for high parity pregnant women on ANC visit coverage.